Menginternalisasi Nilai – Nilai Etika Profesi Guru Melalui Pembelajaran Refleksi dan Humanistik - Muanzil Aminatus Sholehah; Imron Fauzi; M. Ilmil Zawawi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to analyze the internalization of teacher professional ethics through reflective learning and a humanistic approach. The background of this research highlights ongoing moral issues in the educational environment, including violence, behavioral deviance, and abuse of authority, which emphasize the need for strengthening teacher ethical values. This research adopts a qualitative approach using library research methods by examining books, scholarly articles, and relevant documents related to teacher ethics, humanistic education, and reflective learning. The findings reveal that teacher professional ethics serve as a moral foundation in educational interactions and act as a guideline for teachers in carrying out their professional responsibilities. Reflective learning and the humanistic approach are proven to effectively support the internalization of ethical values, as they place learners at the center of the learning process, foster empathetic relationships, and create a safe and meaningful learning atmosphere. In the context of Islamic Religious Education, the teacher's roles as educator, role model, facilitator, motivator, and evaluator significantly contribute to the continuous formation of students' moral character. This study affirms that strengthening teacher professional ethics is essential to realizing an educational environment that is moral, ethical, and oriented toward holistic character development.